The human otitis media with effusion: a numerical-based study. Issue 9 (4th July 2017) - Areias, B.; Parente, M. P. L.; Santos, C.; Gentil, F.; Natal Jorge, R. M.
Abstract: Otitis media is a group of inflammatory diseases of the middle ear. Acute otitis media and otitis media with effusion (OME) are its two main types of manifestation. Otitis media is common in children and can result in structural alterations in the middle ear which will lead to hearing losses. This work studies the effects of an OME on the sound transmission from the external auditory meatus to the inner ear. The finite element method was applied on the present biomechanical study. The numerical model used in this work was built based on the geometrical information obtained from The visible ear project. The present work explains the mechanisms by which the presence of fluid in the middle ear affects hearing by calculating the magnitude, phase and reduction of the normalized umbo velocity and also the magnitude and phase of the normalized stapes velocity. A sound pressure level of 90 dB SPL was applied at the tympanic membrane. The harmonic analysis was performed with the auditory frequency varying from 100 Hz to 10 kHz. A decrease in the response of the normalized umbo and stapes velocity as the tympanic cavity was filled with fluid was obtained. The decrease was more accentuated at the umbo.